WOMEN’S COMMODIFICATION ON TIKTOK: A SEMIOTIC STUDY OF “ELBOW STICKING' CHALLENGE (Profetik: Jurnal Komunikasi, 2021)
The use of social media has grown commonplace in today's culture. Every social media user now has a place to call their own in the digital age. Tiktok is one of the most popular and distinctive social media platforms, and it frequently abuses women through its many 'challenges' for content such as elbow sticking challange. This study takes a non-positivistic approach to the phenomena that occur in the society with a critical interpretive approach. Observations done in TikTok activities and engaging in interactions with TikTok users to be able to understand and uncover the commodification practices of women that occur in TikTok. This study revealed how intertextual the commodification of women in Tiktok was using a critical method that leverages Julia Kristeva's post-modern feminist outlook as a conceptual framework. The findings of this study reveal that the body, women, and culture are interwoven and produce meaning, which overrides earlier meanings by establishing new meanings that exploit Tiktok users, particularly women, which is consistent with media evolution, which also influences value meaning.